Heat-resistant adhesive tape

JP7635406B2Active Publication Date: 2025-02-25DENKA CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2023549509
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-09-24
Filing Date
2022-09-15
Publication Date
2025-02-25
Estimated Expiration
2042-09-15

Smart Images

  • Figure 0007635406000001
    Figure 0007635406000001
Patent Text Reader

Abstract

Provided is an adhesive tape with excellent heat resistance. The adhesive tape comprises a vinyl chloride resin-based base material (A) and an adhesive layer (B) laminated onto at least one side of the base material (A). The base material (A) and the adhesive layer (B) contain the same plasticizer (a), and a heating mass reduction rate of the plasticizer (a) after heating at 200ºC for 60 minutes is 1 mass% or less. A content percentage (W1) of the plasticizer (a) in the base material (A) is 25-35 mass%, and a content percentage (W2) of the plasticizer in the adhesive layer (B) and the content percentage (W1) satisfy expression (1) below. (1): |W2 – W1| ≤ 5 mass%
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an adhesive tape having excellent heat resistance. [Background technology]

[0002] Adhesive tapes based on polyvinyl chloride are known as adhesive tapes for bundling electric wires and wiring in automobiles, etc. In recent years, the automotive field has been shifting from gasoline-powered vehicles to electric vehicles and hybrid vehicles that have a smaller environmental impact. As a result, the need for electronics and automated driving in automotive control systems is increasing, and the demand for adhesive tapes for bundling electric wires is also diversifying.

[0003] Electric vehicles and hybrid vehicles are equipped with batteries such as lithium-ion batteries, and a wide variety of electric wires are arranged inside the vehicle to connect the batteries to the engine. In particular, the number of high-voltage cables connecting the batteries to the motor is increasing, and the areas around these high-voltage cables become hot. Furthermore, in recent years, due to the effects of reducing production costs and making vehicles more compact, electric wires are being placed closer to the exhaust pipe, and adhesive tapes with better heat resistance are required.

[0004] As a method for improving the heat resistance of an adhesive tape, for example, Patent Document 1 proposes an adhesive sheet having a substrate made of a resin composition containing a vinyl chloride resin, a resin having an epoxy group, and a plasticizer. Patent Document 1 describes that the obtained adhesive sheet can maintain 70% or more of its adhesive strength even after being left to stand at 50°C for 72 hours. Patent Document 2 proposes an adhesive sheet having a substrate made of polyvinyl chloride and an adhesive layer containing a specific acrylic polymer. Patent Document 2 describes that an adhesive sheet can be obtained that can maintain its holding power even after being left at 70° C. for 5 days.

[0005] [Patent Document 1] Patent Publication No. 2021-046532 [Patent Document 2] JP 2018-127622 A Summary of the Invention

[0006] As mentioned above, in recent years, adhesive tapes for bundling electric wires in automobiles are required to have high heat resistance so that the tape will not crack or peel off even when the electric wires are placed in a high-temperature environment such as near an exhaust pipe. That is, the tape is required to be able to maintain a constant tensile elongation for a long period of time even when placed in a place where the ambient temperature is 100° C. or higher. The adhesive sheets described in Patent Documents 1 and 2 do not have sufficient heat resistance. SUMMARY OF THE PRESENT EMBODIMENTS Accordingly, an object of the present invention is to provide an adhesive tape having excellent heat resistance.

[0007] In order to solve the above problems, the inventors have conducted intensive research and have discovered that, in an adhesive tape comprising a vinyl chloride resin-based substrate and an adhesive layer, an adhesive tape capable of maintaining a constant tensile elongation for a long period of time in a high-temperature atmosphere of 100°C or higher can be obtained by containing the same plasticizer in the substrate and the adhesive layer, and further setting the absolute difference in the plasticizer content between the substrate and the adhesive layer to a specific numerical value or less, and incorporating as the plasticizer a compound whose rate of mass loss on heating is a certain numerical value or less, thereby completing the present invention. That is, the present invention has the following aspects. [1] A pressure-sensitive adhesive tape comprising a vinyl chloride resin-based substrate (A) and a pressure-sensitive adhesive layer (B) laminated on at least one surface of the substrate (A), wherein the substrate (A) and the pressure-sensitive adhesive layer (B) contain the same plasticizer (a), the plasticizer (a) has a thermal mass loss rate of 1 mass% or less after heating at 200°C for 60 minutes, the content (W1) of the plasticizer (a) in the substrate (A) is 25 to 35 mass%, and the content (W2) of the plasticizer (a) in the pressure-sensitive adhesive layer (B) and the content (W1) satisfy the following formula (1): |W2-W1|≦5% by mass...(1) [2] The pressure-sensitive adhesive tape according to [1], wherein the plasticizer (a) contains at least one plasticizer selected from a trimellitic acid ester plasticizer and an adipate polyester plasticizer. [3] The pressure-sensitive adhesive tape according to [1] or [2], wherein the substrate (A) contains polyvinyl chloride having an average degree of polymerization of 500 to 2,000. [4] The pressure-sensitive adhesive tape according to any one of [1] to [3], wherein the substrate (A) contains a metal-based composite stabilizer. [5] The pressure-sensitive adhesive tape according to any one of [1] to [4], wherein the pressure-sensitive adhesive layer (B) contains a tackifier. [6] The adhesive tape according to [5], wherein the tackifier comprises a petroleum resin. [7] The pressure-sensitive adhesive tape according to any one of [1] to [6], wherein the thickness of the substrate (A) is 40 to 450 μm. [8] The pressure-sensitive adhesive tape according to any one of [1] to [7], wherein the pressure-sensitive adhesive layer (B) has a thickness of 5 to 50 μm. [9] The adhesive tape according to any one of [1] to [8], which is used for bundling electric wires.

[0008] According to the present invention, it is possible to provide an adhesive tape having high heat resistance. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] The present invention will be described in detail below, but the present invention is not limited to the following aspects, and can be implemented by making appropriate modifications within the scope that does not impair the effects of the present invention. When a specific description given for one embodiment also applies to other embodiments, the description may be omitted in other embodiments. In addition, the symbol "~" in this specification means "at least or equal to". In other words, "1 to 50" means "at least 1 and at most 50". [Adhesive tape] The pressure-sensitive adhesive tape according to the present invention is an adhesive tape comprising a vinyl chloride resin-based substrate (A) and an adhesive layer (B) laminated on at least one surface of the substrate (A), wherein the substrate (A) and the adhesive layer (B) contain the same plasticizer (a), the plasticizer (a) has a thermal mass loss rate of 1 mass% or less after heating at 200°C for 60 minutes, a content (W1) of the plasticizer (a) in the substrate (A) is 25 to 35 mass%, and the content (W2) of the plasticizer (a) in the adhesive layer (B) and the content (W1) satisfy the following formula (1): |W2-W1|≦5% by mass...(1) The pressure-sensitive adhesive tape according to the present invention has excellent heat resistance. In this specification, "heat resistance" refers to the ability to maintain the tensile elongation before heating within a certain range even after being left in a high-temperature atmosphere of 100°C or higher, preferably 130°C or higher, for 500 hours or more.

[0010] <Vinyl chloride resin base material (A)> The pressure-sensitive adhesive tape according to the present invention comprises a vinyl chloride resin-based substrate (A) (hereinafter referred to as "substrate (A)"). "Vinyl chloride resin-based substrate" means a substrate made of a resin composition containing at least vinyl chloride resin. The substrate (A) contains the same plasticizer (a) as the pressure-sensitive adhesive layer (B). That is, the substrate (A) is made of a resin composition containing at least vinyl chloride resin and plasticizer (a). The plasticizer (a) is the same as that contained in the pressure-sensitive adhesive layer (B).

[0011] (Vinyl chloride resin) Examples of vinyl chloride resins include homopolymers of vinyl chloride (hereinafter referred to as "polyvinyl chloride"), vinyl chloride-vinyl acetate copolymers, vinyl chloride-vinyl acetate alcohol copolymers, vinyl chloride-ethylene copolymers, vinyl chloride-propylene copolymers, vinylidene chloride-vinyl chloride copolymers, etc. These may be used alone or in combination of two or more. Among these, it is preferable to include polyvinyl chloride because it has excellent flexibility, extensibility, and moldability, is versatile, and can be used inexpensively.

[0012] The average polymerization degree of polyvinyl chloride is not particularly limited as long as it has the effect of the present invention. From the viewpoint of processability, the average polymerization degree of polyvinyl chloride resin is preferably 500 to 2,000, more preferably 700 to 1,800, and particularly preferably 1,000 to 1,500. In addition, from the viewpoint that a base material (A) having a superior tensile elongation before heating can be easily obtained by combining with the plasticizer (a), the average polymerization degree of polyvinyl chloride is preferably more than 700 and not more than 2,000, more preferably 1,000 to 1,800, and even more preferably 1,300 to 1,800. The average polymerization degree is a value measured according to JIS K6720-2.

[0013] The resin composition constituting the base material (A) may contain a resin other than vinyl chloride resin (hereinafter, referred to as "other resin"), as long as the effect of the present invention is not impaired. Examples of other resins include polyester resins, polyimide resins, polyamide resins, polyolefin resins, etc. These may be used alone or in combination of two or more. When the base material (A) contains other resins, it is preferable that the amount of the other resins is 20 mass% or less based on the total mass of the base material (A).

[0014] (Plasticizer (a)) The base material (A) contains a plasticizer (a). The plasticizer (a) is a compound whose thermal mass loss rate after heating at 200° C. for 60 minutes is 1% by mass or less. The thermal mass loss rate of the plasticizer can be specifically measured by the following method. (Method for measuring heat mass loss rate) 1 g of plasticizer (mass before heating) is placed in a heat-drying moisture meter (e.g., A&D Co., Ltd., product name "MX-50") and heated at 200°C for 60 minutes. After cooling to room temperature, the mass (g) of the plasticizer after heating is measured. The thermal mass loss rate of the plasticizer is calculated using the following formula (2). Heat mass reduction rate (mass%) = {(mass of plasticizer before heating (g) - mass of plasticizer after heating (g)) / (mass of plasticizer before heating (g))} × 100 (2)

[0015] The thermal mass loss rate of the plasticizer (a) measured by the above method is 1% by mass or less, preferably 0.8% by mass or less, and more preferably 0.6% by mass or less. The lower limit of the thermal mass loss rate of the plasticizer (a) may be 0% by mass. In one embodiment, the thermal mass loss rate of the plasticizer (a) may be 0 to 1% by mass, 0 to 0.8% by mass, or 0 to 0.6% by mass. In another embodiment, the thermal mass loss rate of the plasticizer (a) may be 0.1 to 0.8% by mass, or 0.1 to 0.6% by mass. The thermal mass loss rate may be 0.3 to 0.8% by mass. By using a plasticizer (a) having a thermal mass loss rate of 1% by mass or less, it is possible to suppress the plasticizer from volatilizing or bleeding out from the base material (A) or the pressure-sensitive adhesive layer (B). Furthermore, by blending the same plasticizer (a) in the base material (A) and the adhesive layer (B), the migration of the plasticizer (a) from the base material (A) to the adhesive layer (B) is easily suppressed, and an adhesive tape with excellent heat resistance is obtained. Here, the "same plasticizer (a)" also includes compounds that are the same compound but have different molecular weights (e.g., mass average molecular weight (Mw)). That is, when the plasticizer (a) includes an adipic acid polyester plasticizer described later, the scope of the present invention also includes an embodiment in which the base material (A) and the adhesive layer (B) each include an adipic acid polyester plasticizer with a different Mw. In addition, when the plasticizer (a) is a mixture of multiple plasticizers, the scope of the present invention also includes an embodiment in which the base material (A) and the adhesive layer (B) each include a mixture of the same type of plasticizer. For example, when a mixture of tri-n-octyl trimellitate and adipic acid polyester (Mw: 2,300) described later is blended as the plasticizer (a) in the base material (A), the same mixture may be blended in the pressure-sensitive adhesive layer (B), or a mixture of different types of trimellitic acid triester plasticizers (e.g., a mixture of isooctyl trimellitate and adipic acid polyester (Mw: 2,300)) or a mixture of adipic acid polyesters with different Mws (e.g., a mixture of tri-n-octyl trimellitate and adipic acid polyester (Mw: 2,000)) may be blended in the pressure-sensitive adhesive layer (B).

[0016] The plasticizer (a) preferably contains at least one plasticizer selected from trimellitic acid ester plasticizers and adipic acid polyester plasticizers. By containing such a plasticizer in the substrate (A), the substrate (A) is more likely to have excellent tensile elongation (hereinafter, sometimes simply referred to as "elongation"). In addition, it is easy to obtain an adhesive tape whose elongation is less likely to decrease even when used for a long period of time in a high-temperature environment. It is more preferable that the plasticizer (a) contains only a trimellitic acid ester plasticizer or an adipic acid polyester plasticizer.

[0017] The content (W1) of the plasticizer (a) in the base material (A) is 25 to 35% by mass with respect to the total mass of the base material (A). The content (W1) is preferably 27 to 33% by mass with respect to the total mass of the base material (A), and more preferably 28.5 to 32.5% by mass. In one embodiment, the content (W1) may be 25 to 30% by mass or 30 to 35% by mass with respect to the total mass of the base material (A). When the content (W1) is 25% by mass or more, an adhesive tape having good conformability to electric wires, being less likely to crack or break even after heating, and being less likely to peel off at the ends can be obtained. When the content (W1) is 35% by mass or less, the elongation of the adhesive tape before heating (hereinafter, sometimes referred to as "initial elongation") can be controlled within an appropriate range. In addition, it is easy to suppress the plasticizer (a) from migrating to the adhesive layer (B) and bleeding out from the surface of the adhesive layer. Moreover, an adhesive tape with good film-forming properties can be obtained. In order to obtain a highly heat-resistant adhesive tape, it is important that the content (W1) is 25 to 35 mass%, and the relationship with the content (W2) of the plasticizer (a) in the adhesive layer (B) described below satisfies the following formula (1). Here, the "total mass of the substrate (A)" refers to the total mass of the resin composition constituting the substrate (A). |W2-W1|≦5% by mass...(1) In addition, in formula (1), |W2-W1| means the absolute difference between the content (W1) of plasticizer (a) in the base material (A) and the content (W2) of plasticizer (a) in the adhesive layer (B).

[0018] (Trimellitic acid ester plasticizer) The plasticizer (a) may contain a trimellitic acid ester-based plasticizer. By containing a trimellitic acid ester-based plasticizer having a thermal mass loss rate of 1% by mass or less, an adhesive tape having excellent elongation is easily obtained. In addition, since such a trimellitic acid ester-based plasticizer has a high boiling point and is difficult to volatilize, an adhesive tape having a low elongation rate even when used for a long period of time in a high-temperature environment is easily obtained. The trimellitic acid ester plasticizer contained in the plasticizer (a) is not particularly limited as long as the thermal mass loss rate after heating at 200°C for 60 minutes is 1% by mass or less, as long as the effect of the present invention is achieved. Examples of such trimellitic acid ester plasticizers include, but are not limited to, tri-n-octyl trimellitate, tri-2-ethylhexyl trimellitate, triisooctyl trimellitate, tri-n-nonyl trimellitate, triisononyl trimellitate, tri-n-decyl trimellitate, and triisodecyl trimellitate. In addition, these plasticizers may be used alone or in combination of two or more. Among these, it is preferable to include tri-n-octyl trimellitate. In addition, when one type of trimellitic acid ester plasticizer is blended in the base material (A) as the plasticizer (a), it is preferable to blend the same trimellitic acid ester plasticizer in the adhesive layer (B). In addition, when two or more kinds of the trimellitate ester plasticizers are mixed and blended as the plasticizer (a) in the base material (A), it is preferable to blend the same mixture in the adhesive layer (B). Also, it is possible to blend a completely identical mixture. It is also preferable that the blending ratio of each trimellitate ester plasticizer in the mixture is the same in the base material (A) and the adhesive layer (B).

[0019] The content of the trimellitic ester plasticizer in the plasticizer (a) is preferably 50 to 100% by mass, more preferably 80 to 100% by mass, based on the total mass of the plasticizer (a). In one embodiment, the content of the trimellitic ester plasticizer in the plasticizer (a) may be 50 to 80% by mass, based on the total mass of the plasticizer (a). The plasticizer (a) may be composed of only the trimellitic ester plasticizer.

[0020] (adipic acid polyester plasticizer) The plasticizer (a) may contain an adipic acid polyester-based plasticizer. By containing an adipic acid polyester-based plasticizer having a thermal mass loss rate of 1% by mass or less, it becomes easier to obtain an adhesive tape having excellent elongation. In addition, since such an adipic acid polyester-based plasticizer has a relatively large mass average molecular weight (Mw), it is difficult for the plasticizer to migrate to the adhesive layer (B). Therefore, it is easy to obtain an adhesive tape whose elongation rate is unlikely to decrease even when used for a long period of time in a high-temperature environment. The adipic acid polyester plasticizer contained in the plasticizer (a) is not particularly limited as long as the thermal mass loss rate after heating at 200°C for 60 minutes is 1% by mass or less, as long as the effect of the present invention is achieved. Examples of such adipic acid polyester plasticizers include, but are not limited to, adipic acid-propylene glycol polyesters and adipic acid-butylene glycol polyesters having Mw in the range of 1,000 to 4,100. The Mw is preferably 1,600 to 4,100, more preferably 2,000 to 4,100. The Mw may be in the range of 1,000 to 3,000, 1,000 to 2,800, or 1,000 to 2,500. The Mw of the polyester adipic acid plasticizer refers to a value measured using gel permeation chromatography (GPC) (e.g., manufactured by Tosoh Corporation) with a total of four GPC columns, two of which are Shodex Corporation's trade names "KF-806L" and one each of "KF-802" and "KF-801", connected in the order of KF-806L, KF-806L, KF-802, and KF-801 from the upstream side, and tetrahydrofuran for high performance liquid chromatography (stabilizer-free) (e.g., manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) as the mobile phase, under conditions of a flow rate of 1.0 milliliter / minute, a column temperature of 40°C, a sample concentration of 1 milligram / milliliter, and a sample injection amount of 100 microliters.

[0021] The polyester adipic acid plasticizer may be a commercially available product, such as a product name "Polysizer (registered trademark) W-4010" (Mw 4,010) manufactured by DIC Corporation. The adipic acid polyester plasticizer contained in the plasticizer (a) may be one type alone or a mixture of two or more types. As described above, the base material (A) and the adhesive layer (B) may contain adipic acid polyester plasticizers with different Mw as the plasticizer (a). When a mixture of adipic acid polyester plasticizers is used as the plasticizer (a), it is preferable to also contain the same mixture in the adhesive layer (B). It is also possible to contain a completely identical mixture. It is also preferable that the ratio of each adipic acid polyester plasticizer in the mixture is the same in the base material (A) and the adhesive layer (B).

[0022] The content of the adipic acid polyester plasticizer in the plasticizer (a) is preferably 50 to 100 mass% based on the total mass of the plasticizer (a), and more preferably 80 to 100 mass%. In one embodiment, the content of the adipic acid polyester plasticizer in the plasticizer (a) may be 50 to 80 mass% based on the total mass of the plasticizer (a). The plasticizer (a) may be composed of only the adipic acid polyester plasticizer.

[0023] The total amount of plasticizer (a) contained in the entire pressure-sensitive adhesive tape ([{(content (W1) (mass %) × thickness of substrate (A) (μm)) + (content (W2) (mass %) × thickness of adhesive layer (B) (μm))} ÷ total thickness of adhesive tape (μm)]) is preferably 25 to 35 mass %, more preferably 28.5 to 32.5 mass %, from the viewpoints of the extensibility and abrasion resistance of the substrate (A) and the adhesive strength and tack of the adhesive. Alternatively, the total amount may be 30 to 35 mass %.

[0024] (Metal-based compound stabilizer) The substrate (A) preferably contains a metal-based composite stabilizer. By containing the metal-based composite stabilizer, thermal deterioration of the tape is suppressed, and the tensile elongation after heating tends to be good. The metal-based composite stabilizer is preferably a hydrotalcite-based compound. The hydrotalcite-based compound contains a divalent metal ion (M 2+ ), trivalent metal ions (M 3+ ), hydroxide ion (OH -) and n-valent anions (A n- ) and, for example, a compound represented by the following general formula (3) can be used. (M 2+ ) X (M 3+ ) Y (OH - ) Z (A n- ) 2 / n mH2O (3) In the general formula (3), X is preferably 3 or more and 8 or less, Y is preferably 1 or more and 4 or less, Z is preferably 8 or more and 16 or less, m is preferably 1 or more and 6 or less, and n is preferably 1 or more and 4 or less. These hydrotalcite-based compounds may be used alone or in combination of two or more kinds.

[0025] In the general formula (3), a divalent metal ion (M 2+ ) include, for example, alkaline earth elements, transition metal elements, and Group 12 elements. Among these, magnesium ions, calcium ions, iron ions, cobalt ions, nickel ions, copper ions, and zinc ions are preferred, and magnesium ions (Mg 2+ ), calcium ion (Ca 2+ ) and zinc ions (Zn 2+ It is more preferable that the metal ion contains at least one metal ion selected from (M 2+ ) may be one type or a combination of two or more types. Trivalent metal ions (M 3+ Examples of the ions (Al) include Group 13 elements, transition metal elements, and Group 3 elements. Specifically, aluminum ions, trivalent iron ions, trivalent cobalt ions, trivalent chromium ions, trivalent manganese ions, and scandium ions are preferred, and aluminum ions (Al 3+ It is more preferable that the compound contains (M 3+ ) may be one type or a combination of two or more types. n-valent anion (A n-) may be, for example, a monovalent halogen ion, a divalent group 16 element ion, a monovalent or higher inorganic acid ion, or a monovalent or higher organic acid ion. - , Cl - , Br - , I - , NO2 - , NO3 - , ClO4 - , CO3 2- , SiO3 2- , SO4 2- , CH3COO - , C6H5COO - , C2H2(COO)2 2- , O 2- , S 2- , Se 2- , Te 2- , PO4 3- , BO3 3- is preferred, and carbonate ion (CO3 2- It is more preferable that the compound contains (A n- ) may be one type or a combination of two or more types.

[0026] The proportion of the metal-based composite stabilizer in the substrate (A) is preferably 0.5 to 5 mass %, more preferably 1 to 3 mass %, based on the total mass of the substrate (A). If the proportion of the metal-based composite stabilizer is within the above range, deterioration of the substrate due to heating is suppressed, and the effect of improving the tensile elongation after heating can be easily obtained.

[0027] (Other additives) The substrate (A) may contain other additives as long as the effects of the present invention are not impaired. Examples of other additives include plasticizers other than the plasticizer (a) (hereinafter referred to as "other plasticizers"), inorganic fillers, modifiers, dispersants, colorants, light absorbers, lubricants, antiblocking agents, and antistatic agents.

[0028] Examples of other plasticizers include phthalate ester plasticizers, phosphoric acid plasticizers, epoxy plasticizers, chlorinated paraffin, etc. These may be used alone or in combination of two or more. From the viewpoint of more easily improving the heat resistance of the resulting pressure-sensitive adhesive tape, it is preferable that the substrate (A) does not contain other plasticizers.

[0029] The base material (A) may contain an inorganic filler. By containing an inorganic filler, the effect of improving processability can be easily obtained. Examples of inorganic fillers include aluminum hydroxide, magnesium hydroxide, zirconium hydroxide, calcium hydroxide, potassium hydroxide, barium hydroxide, ammonium polyphosphate, polyphosphate amide, zirconium oxide, magnesium oxide, zinc oxide, titanium oxide, molybdenum oxide, guanidine phosphate, smectite, zinc borate, anhydrous zinc borate, zinc metaborate, barium metaborate, antimony oxide, antimony trioxide, antimony pentoxide, red phosphorus, talc, kaolin, clay, alumina, silica, boehmite, bentonite, sodium silicate, calcium silicate, calcium sulfate, calcium carbonate, magnesium carbonate, and carbon black. These may be used alone or in combination of two or more. Of these, from the viewpoint of economic efficiency, it is preferable to contain calcium carbonate as the inorganic filler. The blending amount of the inorganic filler is preferably from 0 to 50 mass %, more preferably from 5 to 10 mass %, based on the total weight of the base material (A).

[0030] Examples of the modifier include chlorinated polyethylene, ethylene-vinyl acetate copolymer, acrylonitrile-butadiene-styrene copolymer, methyl methacrylate-butadiene-styrene copolymer, methyl methacrylate-butyl acrylate copolymer, etc. These may be used alone or in combination of two or more.

[0031] When additives other than the above-mentioned plasticizers, inorganic fillers, and modifiers are added, the amount of the additives is not particularly limited as long as the effects of the present invention are not impaired. For example, the amount of the additives may be 15% by mass or less, more preferably 10% by mass or less, and even more preferably 0.01 to 5% by mass, based on the total mass of the base material (A).

[0032] The tensile elongation of the substrate (A) measured under the conditions of JIS C 2107 (specifically, the conditions of Section 8 "Tensile strength and elongation at break") is preferably 100% or more, and more preferably 150% or more. The substrate (A) according to the present invention contains 25 to 35% by mass of the above-mentioned plasticizer (a), and thus has an initial elongation within a proper range compared to conventional substrates, and is more likely to suppress migration of the plasticizer to the pressure-sensitive adhesive layer (B). By providing such a substrate (A), a pressure-sensitive adhesive tape having excellent heat resistance can be easily obtained.

[0033] The thickness of the substrate (A) is not particularly limited as long as it has the effect of the present invention. From the viewpoint of workability as a tape, the thickness is preferably 40 to 450 μm, more preferably 80 to 400 μm, and even more preferably 125 to 300 μm. In one embodiment, the thickness of the substrate (A) may be 40 to 300 μm or 80 to 300 μm. The thickness of the substrate (A) can be measured using a thickness gauge (for example, manufactured by Mitutoyo Corporation).

[0034] <Adhesive layer (B)> The pressure-sensitive adhesive tape according to the present invention includes a pressure-sensitive adhesive layer (B) laminated on at least one surface of a substrate (A). The pressure-sensitive adhesive layer (B) is a layer made of a pressure-sensitive adhesive composition and contains the same plasticizer (a) as the substrate (A). That is, the pressure-sensitive adhesive layer (B) is made of a pressure-sensitive adhesive composition containing at least a pressure-sensitive adhesive component and a plasticizer (a). The thickness of the pressure-sensitive adhesive layer (B) is preferably 5 to 50 μm, and more preferably 10 to 40 μm, from the viewpoints of exerting adhesive strength and maintaining the structure of the pressure-sensitive adhesive layer. In one embodiment, the thickness of the pressure-sensitive adhesive layer (B) may be 20 to 50 μm or 20 to 40 μm.

[0035] The content (W2) of the plasticizer (a) contained in the pressure-sensitive adhesive layer (B) can be adjusted within a range that satisfies the following formula (1). |W2-W1|≦5% by mass...(1) For example, when the content (W1) of the plasticizer (a) in the base material (A) is 25% by mass, the content (W2) of the plasticizer (a) in the pressure-sensitive adhesive layer (B) can be within a range of 20 to 30% by mass with respect to the total mass of the pressure-sensitive adhesive layer (B). When the content (W1) is 35% by mass, the content (W2) can be within a range of 30 to 40% by mass. That is, the content (W2) is preferably within a range of 20 to 40% by mass, more preferably 25 to 35% by mass. By blending the same plasticizer (a) as that in the base material (A) in the pressure-sensitive adhesive layer (B) such that the absolute difference between the content (W1) and the content (W2) is 5% by mass or less, a pressure-sensitive adhesive tape having excellent heat resistance can be obtained. In this specification, the term "total mass of the pressure-sensitive adhesive layer (B)" refers to the total mass of the pressure-sensitive adhesive composition constituting the pressure-sensitive adhesive layer (B). Moreover, the absolute difference (|W2-W1|) between the content (W2) and the content (W1) is preferably 4.5% by mass or less, more preferably 4% by mass or less, and further preferably 0 to 3% by mass. In one embodiment, |W2-W1| may be 0 to 5% by mass, 0 to 4% by mass, 1 to 4% by mass, or 2 to 4% by mass.

[0036] The plasticizer (a) contained in the pressure-sensitive adhesive layer (B) is the same as that contained in the substrate (A). In one embodiment, the plasticizer (a) contained in the substrate (A) and the pressure-sensitive adhesive layer (B) is preferably tri-n-octyl trimellitate or an adipic acid polyester having an Mw of 2,000 to 4,100.

[0037] The pressure-sensitive adhesive layer (B) is composed of a pressure-sensitive adhesive composition containing at least a pressure-sensitive adhesive component and a plasticizer (a). The adhesive component contained in the adhesive composition constituting the adhesive layer (B) is not particularly limited as long as it has the effect of the present invention, and any adhesive that is used in conventional adhesive tapes can be used appropriately.Specifically, the adhesive can be, for example, an acrylic adhesive, a rubber adhesive, a silicone adhesive, a urethane adhesive, etc.

[0038] As the acrylic pressure-sensitive adhesive, for example, one containing an acrylic polymer as a main component can be used. Examples of the acrylic polymer include a polymer of an alkyl (meth)acrylate ester and a polymer of a carboxyl group-containing unsaturated monomer, etc. Here, "(meth)acrylic acid" means acrylic acid and methacrylic acid. Examples of (meth)acrylic acid alkyl esters include methyl acrylate, methyl methacrylate, ethyl acrylate, ethyl methacrylate, n-propyl acrylate, n-propyl methacrylate, isopropyl acrylate, isopropyl methacrylate, n-butyl acrylate, n-butyl methacrylate, isobutyl acrylate, isobutyl methacrylate, sec-butyl acrylate, sec-butyl methacrylate, tert-butyl acrylate, tert-butyl methacrylate, 2-ethylhexyl acrylate, 2-ethylhexyl methacrylate, n-octyl acrylate, n-octyl methacrylate, isooctyl acrylate, isooctyl methacrylate, n-nonyl acrylate, n-nonyl methacrylate, isononyl acrylate, isononyl methacrylate, etc. These may be used alone or in combination of two or more.

[0039] The carboxyl group-containing unsaturated monomer is not particularly limited as long as it is copolymerizable with the above-mentioned (meth)acrylic acid alkyl ester and has the effect of the present invention, and for example, acrylic acid, methacrylic acid, itaconic acid, fumaric acid, maleic acid, etc. can be used. These may be used alone or in combination of two or more.

[0040] The acrylic polymer may be a copolymer containing other monomers in addition to the alkyl (meth)acrylates and carboxy-containing unsaturated monomers exemplified above. Examples of other monomers include hydroxyl group-containing monomers such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, and hydroxyhexyl (meth)acrylate; nitrogen-containing (meth)acrylates such as (meth)acrylamide, acryloylmorpholine, and (meth)acrylonitrile; vinyl acetate, styrene, vinylidene chloride, and vinyl propionate. These may be used alone or in combination of two or more.

[0041] Examples of the rubber-based adhesive include adhesives containing at least one rubber component selected from natural rubber (NR) and synthetic rubber. Examples of synthetic rubbers include at least one selected from the group consisting of styrene-isoprene-styrene block copolymers (SIS), styrene-butadiene-styrene block copolymers (SBS), hydrogenated products of the styrene-based block copolymers (SIPS, SEBS), styrene-butadiene rubber (SBR), polyisoprene rubber (IR), polyisobutylene (PIB), chloroprene rubber (CR), and butyl rubber (IIR), etc. Among these, it is preferable to include SBR from the viewpoints of the cohesiveness of the adhesive and the heat resistance of the tape.

[0042] Examples of silicone-based adhesives include silicone rubber appropriately mixed with silicone resin, silicone oil, and the like.

[0043] Examples of urethane-based adhesives include those obtained by reacting a polyol, such as a polyether-based polyol or a polyester-based polyol, with a polyisocyanate, such as tolylene diisocyanate (TDI), diphenylmethane diisocyanate (MDI), hexamethylene diisocyanate (HDI), or xylylene diisocyanate (XDI).

[0044] It is preferable to use a pressure-sensitive adhesive component in the pressure-sensitive adhesive layer (B) that is easy to develop adhesive strength, has low solubility in the plasticizer (a), and is easy to swell. By using a pressure-sensitive adhesive component that is low in solubility in the plasticizer (a) and is easy to swell with the plasticizer (a), it is easy to prevent the plasticizer (a) from remaining on the surface of the pressure-sensitive adhesive layer (B) and reducing the adhesive strength while maintaining its structure. From this perspective, it is preferable to use a rubber-based pressure-sensitive adhesive component.

[0045] The rubber-based adhesive may contain a graft copolymer in which a (meth)acrylic acid alkyl ester is grafted to the rubber component. In one preferred embodiment, the adhesive may contain a methacrylic acid alkyl ester grafted natural rubber in which a methacrylic acid alkyl ester is grafted to a natural rubber. The mass ratio of the methacrylic acid alkyl ester to the natural rubber in the grafted natural rubber (methacrylic acid alkyl ester / natural rubber) may be in the range of 3 / 97 to 30 / 70, may be in the range of 3 / 97 to 24 / 76, or may be in the range of 3 / 97 to 18 / 82. Moreover, as the methacrylic acid alkyl ester, methyl methacrylate is particularly preferred. In a more preferred embodiment, a mixture of a synthetic rubber and a methacrylic acid alkyl ester grafted natural rubber may be used. By using such a mixture, the aging resistance is likely to be improved. The mass ratio of the synthetic rubber to the grafted natural rubber in the mixture (synthetic rubber / grafted natural rubber) may be in the range of 20 / 80 to 80 / 20.

[0046] The pressure-sensitive adhesive layer (B) may contain any additive other than the pressure-sensitive adhesive component and the plasticizer (a). Examples of additives include the above-mentioned other plasticizers, softeners, tackifiers, surfactants, surface lubricants, leveling agents, antioxidants, corrosion inhibitors, light stabilizers, ultraviolet absorbers, heat stabilizers, polymerization inhibitors, silane coupling agents, lubricants, inorganic or organic fillers, metal powders, pigments, etc. These may be used alone or in combination of two or more. Among these, from the viewpoint of easily obtaining an adhesive tape with excellent heat resistance, it is preferable that the adhesive layer (B) does not contain other plasticizers.

[0047] Examples of tackifiers include petroleum resins such as aliphatic copolymers, aromatic copolymers, aliphatic-aromatic copolymers, and alicyclic copolymers; coumarone-indene resins; terpene resins, terpene phenol resins, and rosin resins such as polymerized rosin; (alkyl)phenol resins; xylene resins; and hydrogenated versions of these. These may be used alone or in combination of two or more. In the pressure-sensitive adhesive tape according to the present invention, the pressure-sensitive adhesive layer (B) preferably contains a tackifier, more preferably a petroleum resin. By containing a tackifier, the pressure-sensitive adhesive tape is likely to have good tack while maintaining its heat resistance. The proportion of the tackifier in the pressure-sensitive adhesive layer (B) is preferably 35 to 40 mass %, more preferably 36 to 38 mass %, based on the total mass of the pressure-sensitive adhesive composition.

[0048] <Middle Class> The pressure-sensitive adhesive tape according to the present invention may have an intermediate layer between the substrate (A) and the pressure-sensitive adhesive layer (B). The intermediate layer is preferably laminated directly on one surface of the substrate (A). Examples of the resin composition constituting the intermediate layer include the above-mentioned methyl methacrylate grafted natural rubber, etc. When the intermediate layer is provided, the thickness thereof is preferably 0.2 to 2.0 μm, more preferably 0.3 to 1.0 μm, from the viewpoints of adhesion between the substrate (A) and the pressure-sensitive adhesive layer (B) and maintaining the structure of the intermediate layer.

[0049] The total thickness of the pressure-sensitive adhesive tape according to the present invention is preferably from 85 to 450 μm, and more preferably from 135 to 340 μm.

[0050] [Adhesive tape manufacturing method] The pressure-sensitive adhesive tape according to the present invention can be produced, for example, by a method including the following steps. A resin composition is prepared by melt-kneading a polyvinyl chloride resin, a plasticizer (a), a metal-based composite stabilizer if necessary, and other additives in a blend such that the content (W1) of the plasticizer (a) is 25 to 35% by mass, so that the components are uniformly dispersed, using a Banbury mixer or the like. Then, a film is formed using a calendar molding machine or the like to form a substrate (A) having a predetermined thickness, width, and length. Then, the above-mentioned adhesive, the plasticizer (a), a tackifier if necessary, and other additives are mixed so that the content (W2) of the plasticizer (a) satisfies the above formula (1) to prepare an adhesive composition, and then the adhesive composition is directly applied to at least one surface of the substrate (A) to form an adhesive layer (B), thereby producing an adhesive tape. The adhesive layer (B) may be formed by transferring the adhesive composition, which has been applied to a separate sheet, to the substrate (A). Examples of methods for applying the pressure-sensitive adhesive composition to the substrate (A) or another sheet include roll coating, spray coating, gravure coating, reverse coating, rod coating, bar coating, die coating, kiss coating, reverse kiss coating, and air knife coating.

[0051] If necessary, an intermediate layer may be provided between the substrate (A) and the pressure-sensitive adhesive layer (B). When providing an intermediate layer, the substrate (A) is formed by the above-mentioned method, and then the resin composition constituting the intermediate layer is applied by a method such as gravure coating to form the intermediate layer on the substrate (A). Then, the pressure-sensitive adhesive composition is applied on the intermediate layer, or the pressure-sensitive adhesive composition applied to another sheet is transferred onto the intermediate layer to form the pressure-sensitive adhesive layer (B), or the like, to produce a pressure-sensitive adhesive tape.

[0052] However, when electric wires bound with a conventional adhesive tape are placed in a high-temperature environment such as near the exhaust pipe of an automobile, cracks may occur in the base material of the adhesive tape over time, or the ends of the tape binding the electric wires may peel off. When the adhesive tape is placed in a place that is likely to become hot, such as near the exhaust pipe of an automobile, it is believed that the plasticizer contained in the adhesive tape gradually volatilizes or bleeds out, causing the tape base material to harden, resulting in cracks and peeling. In response to this, for example, a plasticizer with a high boiling point may be blended into the base material to suppress the volatilization and bleed out. However, this method does not provide sufficient heat resistance. The reason for this is believed to be that the plasticizer migrates from the base material to the adhesive layer, resulting in a decrease in the content of the plasticizer in the base material. As a result of intensive research, the inventors of the present application have found that <1> The base material and the pressure-sensitive adhesive layer contain a plasticizer (a) whose thermal mass loss rate after heating at 200°C for 60 minutes is equal to or less than a certain value. <2> The same plasticizer (a) is blended in the substrate and the adhesive layer, and the absolute difference in the amount of the plasticizer (a) contained in the substrate and the adhesive layer is within a certain range. <3> It has been found that by setting the content of the plasticizer (a) in the substrate within a certain range, it becomes easier to suppress the migration of the plasticizer from the substrate to the adhesive layer, thereby improving the heat resistance of the adhesive tape. <1> ~ <3> It is believed that the inclusion of the plasticizer in the composition reduces the concentration gradient of the plasticizer between the substrate and the adhesive layer, making it difficult for the plasticizer to migrate. As a result, it is believed that the concentration of the plasticizer (a) in the substrate is less likely to decrease even under high temperature conditions, making it possible to maintain a constant tensile elongation. Furthermore, the inventors of the present application have found that the tensile elongation of the substrate (A) is also improved by blending the plasticizer (a) into the substrate (A). By improving the tensile elongation of the substrate (A), it becomes easier to maintain the elongation of the entire tape even after heating.

[0053] As mentioned above, it is considered that the concentration of the plasticizer blended in the adhesive tape, for example, the plasticizer in the substrate, changes over time as it migrates to the adhesive layer or other layers. In the adhesive tape according to the present invention, the content (W1) of the plasticizer (a) in the substrate (A) is the blended amount at the time of manufacture. The absolute difference between the content (W1) and the content (W2) also refers to the value at the time of manufacture. On the other hand, as mentioned above, in the adhesive tape according to the present invention, the plasticizer (a) is unlikely to migrate from the substrate (A) to the adhesive layer (B). Therefore, it is presumed that the content of the plasticizer (a) in each layer can be maintained within a certain range even after manufacture.

[0054] As described above, according to the present invention, <1> ~ <3> By satisfying the above, it is possible to obtain an adhesive tape having excellent heat resistance. The adhesive tape according to the present invention preferably has a retention rate (%) of the adhesive tape after heating at 130° C. for 500 hours ((elongation rate before heating) / (elongation rate after heating)×100) of 50% or more, more preferably 55% or more, and even more preferably 60% or more.

[0055] The adhesive tape according to the present invention has an adhesive strength to SUS measured under the conditions of JIS C 2107 of preferably 0.5 N / 10 mm or more, more preferably 1.0 N / 10 mm or more. Furthermore, the adhesive strength after heating at 120° C. for 168 hours is preferably 1.0 N / 10 mm or more, more preferably 1.5 N / 10 mm or more. The adhesive tape according to the present invention is removably peelable because the substrate (A) is not easily deteriorated even after heating, and a decrease in adhesive strength is easily suppressed. The decrease in adhesive strength due to the use of the adhesive tape for a long period of time under high temperature conditions is considered to be due in part to the seepage (bleed-out) of the plasticizer contained in the adhesive layer onto the adhesive surface. The adhesive tape according to the present invention is easily prevented from bleeding out of the plasticizer from the adhesive surface because the specific plasticizer (a) is blended into both the substrate (A) and the adhesive layer (B). In addition, the plasticizer in the substrate hardens due to the volatilization of the plasticizer, which makes the substrate more susceptible to edge peeling. However, the adhesive tape according to the present invention is easily prevented from volatilizing the plasticizer from the substrate (A) by including the specific plasticizer (a) in the substrate (A). Furthermore, since the substrate (A) is not easily deteriorated, it is easy to maintain flexibility and tape shape even after heating (i.e., the tape can be peeled off again).

[0056] [Application] The pressure-sensitive adhesive tape according to the present invention can be suitably used for bundling and fixing electric wires in the automotive field, bundling and fixing electric wiring in the construction field, etc. As described above, the pressure-sensitive adhesive tape according to the present invention has excellent heat resistance and can therefore be suitably used in applications requiring high heat resistance.

[0057] More preferred aspects of the present invention are as follows. <1> A pressure-sensitive adhesive tape comprising a substrate (A) containing polyvinyl chloride and a pressure-sensitive adhesive layer (B) laminated on at least one surface of the substrate (A), the substrate (A) and the pressure-sensitive adhesive layer (B) contain at least one plasticizer (a) selected from a trimellitic acid ester plasticizer and an adipic acid polyester plasticizer, and the plasticizer (a) contained in the substrate (A) and the pressure-sensitive adhesive layer (B) is the same compound; a pressure-sensitive adhesive tape, wherein the plasticizer (a) has a thermal mass loss rate of 1 mass% or less after heating at 200°C for 60 minutes, the content (W1) of the plasticizer (a) in the base material (A) is 25 to 35 mass%, and the content (W2) of the plasticizer (a) in the pressure-sensitive adhesive layer (B) and the content (W1) satisfy the following formula (1): |W2-W1|≦5% by mass...(1) <2> The pressure-sensitive adhesive layer (B) contains a rubber-based pressure-sensitive adhesive, <1> The adhesive tape according to claim 1. <3> The rubber-based adhesive contains a mixture of synthetic rubber and (meth)acrylic acid alkyl ester grafted natural rubber. <2> The adhesive tape according to claim 1. <4> The plasticizer (a) is a trimellitic acid ester plasticizer or an adipic acid polyester. <1> from <3> 2. The pressure-sensitive adhesive tape according to claim 1 . <5> The substrate (A) contains a metal-based composite stabilizer, and the pressure-sensitive adhesive layer (B) contains a tackifier. <1> from <4> 2. The pressure-sensitive adhesive tape according to claim 1 . EXAMPLES

[0058] The present invention will be described in detail below with reference to examples, but the present invention is not limited to the following description.

[0059] [Example 1] <Creating substrate (A)> Polyvinyl chloride (manufactured by Taiyo Vinyl Co., Ltd., product name "TH-1300", average degree of polymerization 1,300) 59% by mass, tri-n-octyl trimellitate (plasticizer (a), manufactured by DIC Corporation, product name "Monocizer W-750") 29% by mass, metal-based composite stabilizer (Ca-Zn-Mg-based composite powder stabilizer, manufactured by Sakai Chemical Industry Co., Ltd., product name "H-6319") 2% by mass, and other additives (calcium carbonate, manufactured by Konoshima Chemical Co., Ltd., product name "Calcise (registered trademark) P") 10% by mass were mixed and kneaded for 5 minutes with a two-roll machine (manufactured by Kansai Roll Co., Ltd.) at a roll temperature of 170°C, to prepare a substrate (A) having a thickness of 125 μm.

[0060] <Creation of adhesive layer (B)> Next, a styrene-butadiene copolymer latex (SBR, manufactured by E-Tech Co., Ltd., product name "KT-4615B") and a graft copolymer latex obtained by graft polymerization of methyl methacrylate to natural rubber (MMA graft natural rubber, manufactured by Resitex Co., Ltd., product name "MG40S") were mixed to obtain a latex mixture (mass ratio (SBR / MMA graft natural rubber) = 60 / 40) of 33 mass%, tri-n-octyl trimellitate (plasticizer (a)) of 27 mass%, tackifier resin (C5 emulsion petroleum resin, manufactured by Arakawa Chemical Co., Ltd., product name "AP-2100-NT") of 38 mass%, and other additives (sodium diphenyl ether disulfonate, manufactured by Kao Corporation, product name "Pelex (registered trademark) SS-H") of 2 mass%, to obtain a pressure-sensitive adhesive composition. This adhesive composition was applied to the surface of the above-mentioned substrate (A) and dried in an oven at 110° C. for 1 minute to prepare an adhesive tape having a substrate (A) with a thickness of 125 μm and an adhesive layer (B) with a thickness of 20 μm. This adhesive tape was wound into a roll and then heat-treated at 110° C. for 2 hours.

[0061] The adhesive strength and heat resistance of the obtained adhesive tape were evaluated by the following methods. The tensile elongation of the substrate (A) produced in each example was also evaluated. Furthermore, the thermal mass loss rate of the plasticizer used in each example was measured under the following conditions. The results are shown in Table 1.

[0062] (Measurement of tensile elongation of substrate (A)) The tensile elongation of the substrate (A) was measured according to the conditions of "Section 8: Tensile strength and elongation at break" of JIS C 2107.

[0063] (Measurement of adhesive strength of adhesive tape) The adhesive strength of the adhesive tape before heating was measured according to the conditions of "Section 8: Tensile strength and elongation at break" of JIS C 2107. Next, the adhesive tape was placed in a Gear oven (manufactured by Toyo Seiki Seisakusho Co., Ltd.) and heated at 120°C for 168 hours. After that, it was allowed to cool to room temperature, and the adhesive strength after heating was measured in the same manner as before heating. The adhesive strength before and after heating was evaluated according to the following evaluation criteria. Also, adhesive strength before and after heating that was rated B or higher was considered to have passed. (Evaluation criteria: before heating) A: Adhesive strength is 1.4N / 10mm or more B: Adhesive strength is 1.0N / 10mm or more and less than 1.4N / 10mm C: Adhesive strength is less than 1.0N / 10mm (Evaluation criteria: after heating) A: Adhesive strength is 1.5N / 10mm or more B: Adhesive strength is 1.3N / 10mm or more and less than 1.5N / 10mm C: Adhesive strength is less than 1.3N / 10mm

[0064] (Heat resistance 1: Measurement of tensile elongation of adhesive tape) The tensile elongation of the adhesive tape before heating was measured according to the conditions of "Section 8: Tensile strength and elongation at break" of JIS C 2107. Next, the adhesive tape was placed in a gear oven (manufactured by Toyo Seiki Seisakusho Co., Ltd.) and heated at 130°C for 500 hours. After that, it was allowed to cool to room temperature, and the tensile elongation after heating was measured in the same manner as before heating. The tensile elongation before heating and the retention rate of the tensile elongation after heating ((tensile elongation after heating) / (tensile elongation before heating)×100) were evaluated according to the following evaluation criteria. In addition, those with a tensile elongation before heating and a retention rate after heating of B or higher were considered to have passed. (Evaluation criteria: before heating) A: Tensile elongation of 250% or more B: Tensile elongation is 200% or more and less than 250% C: Tensile elongation less than 200% (Evaluation criteria for retention rate) A: Retention rate is 60% or higher B: Retention rate is between 50% and 60% C: Retention rate is less than 50%

[0065] (Heat resistance 2: Electric wire winding test) Ten heat-resistant electric wires for automobiles (manufactured by Sumitomo Wiring Systems, Ltd., product name "AVX050", diameter: 50 mm) cut to a length of 800 mm and four heat-resistant electric wires for automobiles (manufactured by Sumitomo Wiring Systems, Ltd., product name "AVX085", diameter: 85 mm) cut to a length of 800 mm were prepared. These 14 electric wires were bundled and both ends in the longitudinal direction were fixed together with adhesive tape to make it easier to wind them, and then the adhesive tape (width 19 mm) according to each example was wrapped around the outer circumference of the electric wires in a half-wrap to prepare samples for evaluation. Here, "half-wrap winding" refers to wrapping the adhesive tape around the electric wire so that half of the width of the adhesive tape overlaps half of the width of the adhesive tape already wrapped around it. Next, the prepared samples were wrapped once around a cylinder with a diameter of 80 mm and placed in a gear oven (manufactured by Toyo Seiki Seisakusho Co., Ltd.) and heated at 120°C for 168 hours. After that, the adhesive tape was allowed to cool to room temperature, and then peeling at the edges and cracks or breaks were evaluated according to the following evaluation criteria, with a rating of B or higher being considered a pass. (Evaluation criteria: terminal peeling) A: No peeling was observed on the terminals. B: Minor peeling at the terminals (distance of peeling at terminals less than 1.0 mm) was observed. C: Peeling at the terminals (peel distance at terminals 1.0 mm or more) was observed. (Evaluation criteria: cracks, breaks) A: No cracks or breaks were observed. B: Minor cracks or breaks were observed, but the outer surface of the bundled wires was not visible. C: Cracks or breaks were observed that made the outer surface of the bundled electric wires visible.

[0066] (Overall heat resistance rating) The heat resistance of the adhesive tape was evaluated comprehensively according to the following evaluation criteria, based on the evaluations of heat resistance 1 and heat resistance 2. A rating of C or higher was considered a pass. (Evaluation Criteria) A: All heat resistance 1 and heat resistance 2 were rated A. B: The heat resistance 1 and heat resistance 2 ratings include both A and B ratings, but do not include C ratings. C: All of the heat resistance 1 and heat resistance 2 were rated B. D: Includes C rating for heat resistance 1 and heat resistance 2.

[0067] <Measurement of mass loss rate of plasticizer upon heating> 1 g of plasticizer (mass before heating) was placed in a heating type moisture content meter (product name "MX-50" manufactured by A&D Co., Ltd.) and heated at 200°C for 60 minutes. After cooling to room temperature, the mass (g) of the plasticizer after heating was measured. The thermal mass loss rate of the plasticizer was calculated from the following formula (2). Heat mass reduction rate (mass%) = {(mass of plasticizer before heating (g) - mass of plasticizer after heating (g)) / (mass of plasticizer before heating (g)} × 100 (2)

[0068] [Examples 2 to 8, Comparative Examples 1 to 6] Except for the compositions of the substrate (A) and the adhesive layer (B) shown in Table 1, adhesive tapes were produced in the same manner as in Example 1. In Example 7, the thickness of the substrate layer (A) was changed to 300 μm, and in Example 8, the thickness of the adhesive layer (B) was changed to 40 μm. The adhesive tapes of each example were evaluated for adhesive strength and heat resistance in the same manner as in Example 1. The results are shown in Table 1.

[0069] Details of the raw materials listed in Table 1 are as follows. (Vinyl chloride resin) Polyvinyl chloride 1: Polyvinyl chloride (average degree of polymerization 1,300) (manufactured by Taiyo Vinyl Co., Ltd., product name "TH-1300") Polyvinyl chloride 2: Polyvinyl chloride (average degree of polymerization 700) (manufactured by Taiyo Vinyl Co., Ltd., product name "TH-700") Polyvinyl chloride 3: Polyvinyl chloride (average degree of polymerization 1,800) (manufactured by Taiyo Vinyl Co., Ltd., product name "TH-1800") (Plasticizer (a)) Tri-n-octyl trimellitate (manufactured by DIC Corporation, product name "Monocizer W-750", heating mass loss rate (200°C, 60 minutes): 0.48% by mass) Adipic acid polyester (manufactured by DIC Corporation, product name "Polysizer (registered trademark) W-2030", Mw 2,030, heat mass loss rate (200°C, 60 minutes): 0.71% by mass) (Other plasticizers) Diisononyl phthalate (manufactured by J-Plus Corporation, product name "DINP", heat mass loss rate (200°C, 60 minutes): 12.25% by mass) (Adhesive component) Mixed latex: Mixed latex of styrene-butadiene copolymer latex (SBR, manufactured by E-Tech Co., Ltd., product name "KT-4615B") and graft copolymer latex obtained by graft polymerizing natural rubber with methyl methacrylate (MMA graft natural rubber, manufactured by Resitex Co., Ltd., product name "MG40S") (mass ratio (SBR / MMA graft natural rubber) = 60 / 40) (Metal-based compound stabilizer) Ca-Zn-Mg composite powder stabilizer (manufactured by Sakai Chemical Industry Co., Ltd., product name "H-6319") (Other additives) Inorganic filler: calcium carbonate (manufactured by Konoshima Chemical Co., Ltd., product name "Calcise P") Surfactant: Sodium diphenyl ether disulfonate (Kao Corporation, product name "Pelex SS-H")

[0070] [Table 1]

[0071] As shown in Table 1, the pressure-sensitive adhesive tapes of Examples 1 to 8 satisfying the configuration of the present invention had a tensile elongation retention rate of 50% or more even after heating at 130°C for 500 hours. In addition, in the electric wire winding test, the occurrence of terminal peeling, cracks, and breaks was small. On the other hand, the pressure-sensitive adhesive tapes of Comparative Examples 1 and 2, in which the absolute difference between the content (W2) and the content (W1) was 5% by mass or less but the content (W1) was outside the range of 25 to 35% by mass, had a decreased tensile elongation retention rate after heating. In addition, in the pressure-sensitive adhesive tape of Comparative Example 2, the frequency of terminal peeling, cracks, and breaks was high even in the electric wire winding test. In addition, the pressure-sensitive adhesive tapes of Comparative Examples 3 and 4, in which the absolute difference between the content (W2) and the content (W1) was more than 5% by mass, also had a decreased tensile elongation retention rate after heating. In addition, in Comparative Example 5, in which different plasticizers were blended into the base material (A) and the pressure-sensitive adhesive layer (B), the tensile elongation retention rate after heating was also decreased. The adhesive tape of Comparative Example 6, which contains diisononyl phthalate and has a thermal mass loss rate of more than 1% by mass at 200°C for 60 minutes, had the lowest retention rate of tensile elongation after heating, and also had a high frequency of edge peeling, cracks, and breaks in the electric wire winding test. From the above results, it was confirmed that the adhesive tape according to the present invention has excellent heat resistance. [Industrial Applicability]

[0072] The pressure-sensitive adhesive tape according to the present invention can be suitably used for bundling and fixing electric wires in the automotive field, bundling and fixing electric wiring in the construction field, etc. As described above, the pressure-sensitive adhesive tape according to the present invention has excellent heat resistance and can therefore be suitably used in applications requiring high heat resistance.

Claims

1. A pressure-sensitive adhesive tape comprising a vinyl chloride resin-based substrate (A) and a pressure-sensitive adhesive layer (B) laminated on at least one surface of the substrate (A), the substrate (A) and the pressure-sensitive adhesive layer (B) contain the same plasticizer (a), The substrate (A) contains 0.5 to 3 mass% of a metal-based composite stabilizer relative to the total mass of the substrate (A), The plasticizer (a) has a thermal mass loss rate of 1% by mass or less after heating at 200° C. for 60 minutes, a content (W1) of the plasticizer (a) in the base material (A) is 25 to 35 mass %, and a content (W2) of the plasticizer (a) in the pressure-sensitive adhesive layer (B) and the content (W1) satisfy the following formula (1): |W2-W1|≦5% by mass...(1)

2. The pressure-sensitive adhesive tape according to claim 1 , wherein the plasticizer (a) comprises at least one plasticizer selected from the group consisting of trimellitic acid ester plasticizers and adipate polyester plasticizers.

3. 3. The pressure-sensitive adhesive tape according to claim 1, wherein the substrate (A) comprises polyvinyl chloride having an average degree of polymerization of 500 to 2,000.

4. The pressure-sensitive adhesive tape according to claim 1 , wherein the pressure-sensitive adhesive layer (B) contains a tackifier.

5. The adhesive tape according to claim 4 , wherein the tackifier comprises a petroleum resin.

6. The pressure-sensitive adhesive tape according to claim 1 or 2, wherein the substrate (A) has a thickness of 40 to 450 μm.

7. The pressure-sensitive adhesive tape according to claim 1 or 2, wherein the pressure-sensitive adhesive layer (B) has a thickness of 5 to 50 μm.

8. 3. The pressure-sensitive adhesive tape according to claim 1, which is used for bundling electric wires.

Citation Information

Patent Citations

  • Method for producing self-adhesive sheet and self-adhesive sheet

    JP2011032324A

  • High-temperature resistant insulating adhesive tape base material

    JP2016524632A

  • Dicing tape

    JP2017212249A

  • Pressure-sensitive adhesive tape

    WO2018225541A1